2013
DOI: 10.1074/jbc.m113.483172
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of the Insulin Receptor-related Receptor Activation by Alkali

Abstract: Background:The IRR is a member of the insulin receptor family that functions as a sensor of alkaline medium. Results: We have identified key motifs of IRR ectodomain that are involved in alkali sensing. Conclusion: IRR activation by alkali is a complex multipoint process. Significance: Understanding activation of IRR potentially similar to insulin receptor activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…A dose-dependent and time course effect of TM peptides on receptor phosphorylation was detected by Western blot. To detect the total protein as a loading control for phosphorylated receptors, the membrane was stripped with 0.2 M glycine and 1% SDS for 15 min, blocked, and incubated with anti-TrkA, TrkB, TrkC, and FGFR1 antibodies (52,53).…”
Section: In Vitro Phosphorylation Assaymentioning
confidence: 99%
“…A dose-dependent and time course effect of TM peptides on receptor phosphorylation was detected by Western blot. To detect the total protein as a loading control for phosphorylated receptors, the membrane was stripped with 0.2 M glycine and 1% SDS for 15 min, blocked, and incubated with anti-TrkA, TrkB, TrkC, and FGFR1 antibodies (52,53).…”
Section: In Vitro Phosphorylation Assaymentioning
confidence: 99%
“…In vivo experiments using mice with IRR gene knockout demonstrated that this receptor is involved in the regulation of renal excretion of excess alkali in the form of bicarbonate [ 6 , 7 ]. Mapping of the regions determining the pH sensitivity of IRR has shown that several extracellular domains are responsible for receptor activation [ 5 , 8 ], which ensures positive cooperation in activation (the Hill’s coefficient being ~ 2.4) [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The IR family receptors are structurally unique when compared to other RTKs; fully processed IR, IGF1R, and IRR are disulfide-linked preformed dimers, as opposed to monomers that dimerize upon activation [25]. IRR is the least understood within the IR family and has no known ligand, although IRR may act as an extracellular alkali sensor [6]. On the other hand, IR and IGF1R have been extensively studied because of their importance in the regulation of many normal cellular functions, and because of their roles in diseases such as diabetes and cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%